INDONESIA'S SPATIAL DATA INFRASTRUCTURE (CASE STUDY: BANGKALAN, SAMPANG AND BLITAR REGENCIES) - Rahmawati, Hadiyah (Journal of Marine-Earth Science and Technology, 2022)
The paper examines the current state of Spatial Data Infrastructure (SDI) in Indonesia, with a focus on identifying strengths, weaknesses, and organizational structures of the national SDIs. This paper aims to inform the design and implementation of a future regional SDI for the local government especially at the Bangkalan, Sampang and Blitar Regency. The evaluation is conducted using a survey with 46 questions, which assess the factors that affect execution the of SDI in the region. The survey is classified according to the five basic components of an SDI: policy elements, institutional elements, human resources, standard elements, geospatial data and information, and technology elements. The results of the survey are analyzed to identify the current state of SDI implementation in the region and to serve as a reference point for future updates. The paper concludes by highlighting the need for technical and organizational solutions to address present problems in the geospatial data management and interoperability in order to fully exploit the potential of geospatial information in decision making.